The need for justice and the realization of refugee rights in a cris is : the Eastern Zaire question - Katabazi, Judith K. (Kampala : Makerere University, 1998)
Dissertation (LLB) - Makerere University, 1998
Includes bibliographical references (p. 124-127)
Keywords: Refugees -- Legal status, laws, etc; Human rights